Fenomena Bercadar Perempuan Aceh Kontemporer dalam Analisis Sejarah, Budaya dan Teologi - Lukman Hakim (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2023)
The phenomenon of wearing a face veil (bercadar) in Aceh, which has now become a model for Muslim women's attire, is believed to have originated not from local eccentricities but from local traditions. The practice of wearing a face veil represents a newly formed cultural expression in the contemporary religious context of Acehnese Muslim women. This article explores various aspects related to the use of the veil among Muslim women in Aceh today, including the historical emergence of the veil within the socio-cultural context of Acehnese society, the cultural and objective conditions of Acehnese society that allow for the emergence of the veil, and the theological motives underlying the contemporary usage of the veil by Acehnese women. This study is based on observations and interviews. Observations were conducted on the increasing number of women wearing the veil in society, particularly among students at various universities and educational institutions in Aceh. The study indicates that although the veil does not have historical roots in Acehnese fashion, it is still accepted as a new Islamic culture. The use of the veil in Aceh has become a cultural necessity as Aceh opens itself up to a globalized world system, which inevitably leads to intercultural connections. The theological significance of wearing the veil among Acehnese Muslim women also indicates an increased awareness of improving their relationship with the Divine Creator. Therefore, the phenomenon of wearing a face veil as a contemporary fashion style among Acehnese Muslim women to express their religious identity is not bound by local history and even remains open to embracing cultures and expressions of beliefs from outside, as long as those cultures do not contradict Islamic values. Abstrak Bercadar yang kini menjadi sebuah model berpakaian muslimah Aceh diyakini bukan berasal dari tradisi lokal keacehan. Fenomena bercadar merupakan sebuah bentukan budaya baru dalam ekspresi keagamaan muslimah Aceh kontemporer. Artikel membahas beberapa sisi terkait penggunaan cadar di kalangan muslimah Aceh hari ini yang meliputi; sejarah kemunculan cadar dalam konteks sosial budaya masyarakat Aceh, budaya dan kondisi objektif masyarakat Aceh yang memberi ruang kemunculan cadar, dan motif teologi dalam konteks penggunaan cadar perempuan Aceh kontemporer. Kajian ini didasarkan pada observasi dan wawancara. Observasi dilakukan atas fenomena pemakai cadar yang semakin bertambah dalam masyarakat, terutama dari kalangan mahasiswa di beberapa universitas dan lembaga pendidikan lainnya di Aceh. Kajian ini menunjukkan bahwa meskipun cadar tidak memiliki akar sejarah dalam model berbusana di Aceh namun tetap diterima sebagai sebuah budaya baru yang islami. Penggunaan cadar di Aceh menjadi keniscayaan budaya ketika Aceh membuka diri dalam sebuah sistem dunia yang global, yang memungkinkan terjadi keterhubungan antar budaya yang tidak mungkin terelakkan. Penggunaan cadar di kalangan muslimah Aceh ini secara teologis juga menunjukkan peningkatan kesadaran memperbaiki hubungan yang lebih baik dengan khalik. Dengan demikian fenomena bercadar sebagai gaya berpakaian muslimah Aceh kontemporer dalam mengekspresikan identitas keagamaannya tidak terikat oleh sejarah lokal dan bahkan membuka diri untuk menerima budaya dan ekspresi keyakinan yang berasal dari luar selama budaya itu tidak bertentangan dengan nilai-nilai Islam.